2010
DOI: 10.1074/jbc.m109.098780
|View full text |Cite
|
Sign up to set email alerts
|

Axonal Neuregulin 1 Type III Activates NF-κB in Schwann Cells during Myelin Formation

Abstract: The formation of myelin requires a series of complex signaling events initiated by the axon to surrounding glial cells, which ultimately respond by tightly wrapping the axon with layers of specialized plasma membrane thereby allowing for saltatory conduction. Activation of the transcription factor NF-B in Schwann cells has been suggested to be critical for these cells to differentiate into a myelinating phenotype; however, the mechanisms by which it is activated have yet to be elucidated. Here, we demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 50 publications
1
30
0
Order By: Relevance
“…A number of studies have demonstrated that NF-B is essential for myelin formation (especially in the PNS), although sometimes with conflicting results Jessen and Mirsky, 2008;Limpert and Carter, 2010;Limpert et al, 2013;Morton et al, 2013;Nickols et al, 2003;Yoon et al, 2008). Myelin basic protein has been identified as one direct gene target of NF-B (Nickols et al, 2003).…”
Section: Nuclear Factor (Nf)-äb Regulationmentioning
confidence: 98%
“…A number of studies have demonstrated that NF-B is essential for myelin formation (especially in the PNS), although sometimes with conflicting results Jessen and Mirsky, 2008;Limpert and Carter, 2010;Limpert et al, 2013;Morton et al, 2013;Nickols et al, 2003;Yoon et al, 2008). Myelin basic protein has been identified as one direct gene target of NF-B (Nickols et al, 2003).…”
Section: Nuclear Factor (Nf)-äb Regulationmentioning
confidence: 98%
“…Crucially, cAMP appears to switch NRG1 from a proliferative signal to a myelin differentiation signal [62]. A further example of interaction between these pathways is that type III NRG1 and cAMP-dependent PKA phosphorylation act cooperatively to increase the activity of NF-κB, which promotes myelination [69,70].…”
Section: Nrg1 Signaling In Scsmentioning
confidence: 99%
“…A further example of interaction between these pathways is that type III NRG1 and cAMP-dependent PKA phosphorylation act cooperatively to increase the activity of NF-κB, which promotes myelination [69,70].…”
Section: Nrg1 Signaling In Scsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acting through ErbB receptors, NRG1 stimulates SC mitogenesis and myelination through signaling via the ERK and PI3-K pathways, an effect enhanced by cAMP [103,104]. Myelinating effects of NRG1 are also exerted through NF-κB activation [105,106], again enhanced by cAMP [107] as well as MAPK to drive cell proliferation and PI3K/Akt to prevent apoptosis. As mentioned above, Kao described an additional pathway downstream from ErbB, in which NRG1 acts through the protein phosphatase calcineurin to directly Fig.…”
Section: Molecular Mechanisms Underlying the Differentiation Of Neuramentioning
confidence: 97%